MiR-1224 Acts as a Prognostic Biomarker and Inhibits the Progression of Gastric Cancer by Targeting SATB1 - Han, Guo-Dong; Sun, Yuan; Hui, Hong-Xia; Tao, Ming-Yue; Liu, Yang-Qing; Zhu, Jing (Frontiers in Oncology, 2021)
Objective MiR-1224 has been reported to exhibit abnormal expression in several tumors. However, the expressing pattern and roles of miR-1224 in gastric cancer (GC) remain unclear. Our current research aimed to explore the potential involvement of miR-1224 in the GC progression. Materials and Methods The expression of miR-1224 was examined in tissue samples of 128 GC patients and cell lines by RT-PCR. Besides, the associations of miR-1224 expressions with clinicopathologic features and prognosis of GC patients were analyzed. Then, the possible influences of miR-1224 on cell proliferation and cell migration were determined. Afterward, the molecular target of miR-1224 was identified using bioinformatics assays and confirmed experimentally. Finally, RT-PCR and Western blot assays were performed to investigate the effect of the abnormal miR-1224 expression on the EMT and Wnt/β-catenin pathway. Results miR-1224 was lowly expressed in the GC specimens and cell lines due to T classification and TNM stage. Survival assays demonstrated that GC patients with low expressions of miR-1224 possessed poor overall survivals. Moreover, in vitro and in vivo assays revealed that the overexpression of miR-1224 inhibited cell proliferation, migration, and invasion in GC cells. SATB homeobox 1 (SATB1) was verified as a direct target of miR-1224 in GC. Furthermore, β-catenin and c-myc were significantly inhibited in miR-1224-overexpression cells. Conclusions Our findings highlight the potential of miR-1224 as a therapeutic target and novel biomarker for GC patients